2021
DOI: 10.1002/job.2497
|View full text |Cite
|
Sign up to set email alerts
|

Delivering bad news fairly: Higher construal level promotes interactional justice enactment through perspective taking

Abstract: Summary How can managers deliver bad news with greater interactional justice? We propose a novel cognitive pathway: Construing the activity at a higher (vs. lower) level increases actors' other‐oriented perspective taking, which in turn promotes the enactment of interactional justice. Three studies provide support. Studies 1 and 2 demonstrated a beneficial effect of construal level on interactional justice enactment when explaining a hypothetical bad news decision. Study 2 also showed that other‐oriented persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 78 publications
(143 reference statements)
0
10
0
Order By: Relevance
“…The cognitive framing or construction of circumstances can, at a higher level of construal, promote a Kantian deontic, rule‐adhering response (Eyal & Liberman, 2012) or, at a lower level of construal, provide opportunities for motivated attributions or moral disengagement (van Houwelingen et al, 2021). Interestingly, high construal levels do not preclude deliberate information processing, as Holt and colleagues (2021) point out. In their paper, high construal levels facilitate perspective taking and, consequently, fairer processes and interactions.…”
Section: The Conspicuous Absence Of Deontic Motive Morality and Ethicsmentioning
confidence: 97%
See 3 more Smart Citations
“…The cognitive framing or construction of circumstances can, at a higher level of construal, promote a Kantian deontic, rule‐adhering response (Eyal & Liberman, 2012) or, at a lower level of construal, provide opportunities for motivated attributions or moral disengagement (van Houwelingen et al, 2021). Interestingly, high construal levels do not preclude deliberate information processing, as Holt and colleagues (2021) point out. In their paper, high construal levels facilitate perspective taking and, consequently, fairer processes and interactions.…”
Section: The Conspicuous Absence Of Deontic Motive Morality and Ethicsmentioning
confidence: 97%
“…In this vein, van Houwelingen and colleagues (2021) found that justice agents can be more lenient on transgressors whose activities benefitted the justice agent but that this bias is counteracted when the situation is construed at a high level, because low‐level construal provides opportunities to exploit contextual information as mitigating factors. From a similar information processing perspective, Holt and colleagues (2021) demonstrate that construing the situation at a higher rather than lower level broadens managers' mental horizon and promotes perspective taking that is then integrated into justice deliberations.…”
Section: Uncharted Waters: Critical Reflections and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, being inclined to be fair by disposition or even being motivated to be fair is not enough—managers must possess the self-regulatory capacity to engage in justice actions and be aware of their justice behaviors (Whiteside & Barclay, 2016). They must also have the cognitive capacity to take the perspective of the justice recipient (Holt et al, 2021). Context also matters; for example, Sherf et al (2019) demonstrated that when managers have a high workload, justice actions are deprioritized unless the organization explicitly rewards these actions.…”
Section: Current Directions: Two Paradigm Shiftsmentioning
confidence: 99%